A QoS-Aware Multipath Routing Protocol for Wi-Fi Based Long Distance Mesh Networks - Talele, Ajay; Mehta, Prajyot; Gadade, Yogesh; Mundhe, Avinash; Kandhare, Akshay (Asian Journal of Science and Applied Technology, 2018)
Routing plays a crucial role in provisioning Quality of Service (QoS) over WiFi-based Long Distance (WiLD) mesh networks. Traditional routing protocols normally maintain a single optimal path between each pair of source and destination nodes. In gateway-based mesh networks, the optimal paths between gateway and other nodes often overlap and hence degrades the overall network performance significantly. Multipath routing protocols are widely used in Wireless Mess Networks (WMN) for providing QoS to various network applications. Smooth routing of real time traffic with varying QoS requirements is a challenging task. In this paper, we propose a QoS-aware hybrid multipath routing protocol which can discover multiple maximally disjoint paths between a gateway and any other node. The gateway node selects n-best paths for the source node. Before starting a given real time flow, a path selection scheme chooses the appropriate path or set of paths amongst the available discovered paths. To evenly distribute the traffic among the paths chosen, an admission control mechanism has been proposed. In case of significant change in the quality of any discovered paths, a path maintenance process induces the source node to trigger a route update process. The proposed protocol enhances the performance of real time traffic significantly. The simulation results show that the proposed protocol achieves significant improvement in different QoS parameters. With the increase in number of disjoint paths from source to destination, a substantial improvement in throughput and delay is observed.